Intelligent Tutoring System For Mathematical Problems : Explanation Generations For Integration Problem (EGIP) - Thaw, Ta Htaik (2005)
This thesis is concerned with the development of an ITS for teaching mathematics. Generating appropriate problem solving methods and explanations to students (in a friendly format) is crucial in the ITS environment. This research aims to develop a software prototype that will imitate the role of a human tutor in delivering knowledge to learner, in a human-focused approach.